Associations of diet quality, food consumption, eating frequency and eating behaviour with dental caries experience in Finnish children: a 2-year longitudinal study. Issue 8 (28th April 2023) - Virkkala, Veera F.; Eloranta, Aino-Maija; Suominen, Anna Liisa; Vierola, Anu; Ikävalko, Tiina; Väistö, Juuso; Mikkonen, Santtu; Methuen, Mirja; Schwab, Ursula; Viljakainen, Heli T.; Leinonen, Jukka; Närhi, Matti; et al.
Abstract: We examined cross-sectional and longitudinal associations of dietary factors with caries experience in a population sample of 487 children aged 6–9 years at baseline examinations of the Physical Activity and Nutrition in Children (PANIC) Study. Altogether, 406 of these children attended 2-year follow-up examinations. Food consumption and eating frequency were assessed using 4-day food records, diet quality using the Baltic Sea Diet Score (BSDS) and eating behaviour using the Children's Eating Behavior Questionnaire. Caries experience was examined clinically. The cross-sectional associations of dietary factors with caries experience at baseline were analysed using linear regression and the longitudinal associations of dietary factors with a change in caries experience over follow-up using generalised mixed-effects regression adjusted for other risk factors. A higher consumption of high-fibre grain products (standardised regression coefficient β = −0·16, P = 0·003) and milk ( β = −0·11, P = 0·025) and higher BSDS ( β = −0·15, P = 0·007) were associated with lower caries experience, whereas a higher consumption of potatoes ( β = 0·11, P = 0·048) and emotional overeating ( β = 0·12, P = 0·025) were associated with higher caries experience. Higher snacking frequency (fixed coefficient β = 0·07, P = 0·033), desire to drink ( β = 0·10, P = 0·046), slowness in eating ( β = 0·12, P = 0·027) and food fussiness ( β = 0·12, P = 0·018) were associated with higher caries experience, whereas enjoyment of food ( β = −0·12, P = 0·034) and higher BSDS ( β = −0·02, P = 0·051) were associated with lower caries experience.